Quantitative image of fluorescence of ceramic and resin-cement veneers - Francisca Daniele Jardilino SILAMI; Sebastião PRATAVIEIRA; Marcelo Saito NOGUEIRA; Allyson Anne BARRETT; Mário Alexandre Coelho SINHORETI; Saulo GERALDELI; Fernanda de Carvalho Panzeri PIRES-DE-SOUZA (Brazilian Oral Research)
Abstract The main of the study was quantify the effect of two ceramics with two underlying resin cements on apparent fluorescence levels. Buccal surfaces of two bovine incisors were ground flat producing one enamel and one dentin substrate. The veneers were fabricated (0.5 and 1.0 mm thickness) using two ceramics (IPSe.max Press and IPSe.max Zirpress, Ivoclar Vivadent). Veneers were cemented using either light-cured (Variolink II, Ivoclar Vivadent) or self-adhesive dual (Rely X U200, 3M ESPE) cement. The layered Control group materials had no cement application. Semi-quantitative fluorescence image analysis (Matlabs software, Matworks) involved processing the images as captured under each daylight (DL, Gretagmacbeth) and ultraviolet illuminants (UVA, Sylvania) within a neutral-gray lightbox (Macbeth Spectral Light). Statistical analysis of the quantitative fluorescence values was performed using two-way ANOVA and Tukey’s test (p < 0.05). The e.max Zirpress on the dentin substrate produced greater fluorescence (p < 0.05) when subjected to UV illumination and more fluorescence (p < 0.05) than e.max Press in both cement groups. Light-cured cement produced higher (p < 0.05) fluorescence than the dual-cement with e.max Press on enamel under UV illumination. The fluorescence for e.max Press on the dentin substrate was greater (p < 0.05) than for e.max Zirpress using dual self-adhesive cement subjected to daylight illumination. Thus, it is possible to conclude that the combination of ceramic and cement produce definite, significant effects on the apparent fluorescence, vital quality for restorative dentistry.